The Alleviation Of Extreme Poverty In The City Of Padangsidimpuan - Siregar, Deni Afnita; Arbanur Rasyid; Utari Evy Cahyani (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study examines the multidimensional dynamics of extreme poverty alleviation in Padangsidimpuan City, Indonesia, within the framework of Islamic economics. The Sustainable Livelihood Framework (SLF) approach is used as the analytical framework, with Amartya Sen's Capability Approach Theory as the theoretical basis. This study aims to understand how social, institutional, economic, and spiritual capital interact in shaping community resilience and access to basic welfare. The method used is qualitative-empirical with data collection through semi-structured interviews with key stakeholders, such as local government officials, religious leaders, zakat management institutions, and poor households. The analysis was conducted using a thematic content analysis approach. The results of the study show that poverty in Padangsidimpuan is exacerbated by structural limitations, such as limited access to productive assets, weak institutional coordination, and a fragile social protection system. However, the integration of Islamic philanthropic instruments such as zakat, infaq, and waqf into poverty alleviation programs, especially through community-based empowerment models, can significantly increase the economic capability and dignity of beneficiaries. This study emphasizes the importance of value-based governance and synergy between state institutions and religious institutions in addressing extreme poverty sustainably. Scientifically, this study contributes to the development of literature by offering a contextual poverty alleviation model rooted in Islamic economic values, local wisdom, and participatory development paradigms. Practically, this study provides policy recommendations for integrating religious-based economic interventions into the national poverty alleviation framework. These findings provide applicable insights for policymakers and development practitioners in formulating culturally relevant and structurally effective strategies to eradicate extreme poverty.